Etanercept protects rat cardiomyocytes against hypertrophy by regulating inflammatory cytokines secretion and cell apoptosis - Li,Q. (2017)
We aimed to investigate the effect of etanercept, a tumor necrosis factor-α (TNF-α) inhibitor, on rat cardiomyocyte hypertrophy and its underlying mechanism. Primary neonatal rat cardiomyocytes were isolated from Sprague-Dawley rats. The model of rat cardiomyocyte hypertrophy was induced by endothelin, and then treated with different concentrations of etanercept (1, 10, and 50 μM). After treatment, cell counts, viability and cell apoptosis were evaluated. The mRNA levels of myocardial hypertrophy marker genes, including atrial natriuretic factor (ANF), matrix metalloproteinase (MMP)-9 and MMP-13, were detected by qRT-PCR, and the expressions of apoptosis-related proteins (Bcl-2 and Bax) were measured by western blotting. The protein levels of transforming growth factor-β1 (TGF-β1), interleukin (IL)-1β, IL-6, leukemia inhibitory factor (LIF) and cardiotrophin-1 (CT-1) were determined using enzyme linked immunosorbent assay (ELISA) kits. In the present study, TNF-α level in cardiomyocytes with hypertrophy was significantly enhanced (P<0.05). Compared to the model group, cell number and viability were significantly increased and ratio of apoptotic cells was reduced by etanercept (P<0.05, P<0.01, or P<0.001). In addition, etanercept remarkably reduced the mRNA levels of ANF, MMP-9 and MMP-13, inhibited the expression of Bax, and increased the expression of Bcl-2 compared to the model group (P<0.05). ELISA results further showed that etanercept lowered the levels of IL-1β, IL-6, LIF and CT-1 but not TGF-β1 compared to the model group (P<0.05). Etanercept may protect rat cardiomyocytes from hypertrophy by inhibiting inflammatory cytokines secretion and cell apoptosis.